Odpowiedź:
2(x+3) = 10
2x+6 = 10 |-6
2x = 4 |:2
x = 2
3(x-1)+2 = 8
3x-3+2 = 8
3x = 8+3-2
3x = 9 |:3
x = 3
2(10-2x) = 16
20-4x = 16 |-20
-4x = -4 |:(-4)
x = 1
5-2(x+2) = 9
5-2x-4 = 9
-2x = 9-5+4
-2x = 8 |:(-2)
x = -4
-3(6-2x) = 4x
-18+6x = 4x |-6x
-18 = -2x
-2x = -18 |:(-2)
x = 9
5(x+4)-2x+3 = 2(1-2x)
5x+20-2x+3 = 2-4x
5x-2x+4x = 2-20-3
7x = -21 |:7
x = -3
4(x-2)-2(x-4) = 5(x+1)-3x
4x-8-2x+8 = 5x+5-3x
4x-2x-5x+3x = 5+8-8
0x = 5 |:0
x = 0
4(3x+2)+5(2x+3) = -2x-13
12x+8+10x+15 = -2x-13
12x+10x+2x = -13-8-15
24x = -36 |:24
x = -1,5
Proszę :)
Szczegółowe wyjaśnienie: